RBF neural network disturbance observer-based backstepping boundary vibration control for Euler–Bernoulli beam model with input saturation - Zhong, Jiaqi; Zhang, Jing; Chen, Xiaolei; Wang, Dengpan; Yuan, Yupeng (ISA transactions, 2024)
The main objective of this paper is to address the issue of vibration control for a class of Euler–Bernoulli beam systems that are subject to external disturbances and input saturation. The proposed controller differs from other backstepping methods in that it employs a radial basis function (RBF) neural network to accurately estimate boundary disturbances and incorporates the hyperbolic tangent function to ensure input constraints. The nonlinear partial differential equation (PDE) model is initially derived based on Hamilton’s principle to capture the dominant dynamic characteristics of the flexible beam. In the framework of the Lyapunov direct approach, an adaptive RBF neural network-based law is subsequently designed to estimate the state-related boundary disturbances. The backstepping approach is then developed to propose sufficient conditions for ensuring the stability and convergence of closed-loop systems subject to input saturation. Finally, the effectiveness and superiority of the proposed methodology are further demonstrated by comparing the simulation results of constrained backstepping controllers. [Display omitted] •The paper addresses the issue of vibration control for Euler–Bernoulli beam models.•This system is susceptible to unknown external disturbances and input saturation.•A constrained boundary controller is developed based on backstepping technology.•An RBF neural network observer is proposed to estimate the boundary disturbances.•The closed-loop stability is established by considering the above constraints.